Red fruit (Pandanus conoideus Lam) oil stimulates nitric oxide production and reduces oxidative stress in endothelial cells. (December 2018) - Xia, Ning; Schirra, Christian; Hasselwander, Solveig; Förstermann, Ulrich; Li, Huige
Graphical abstract: Highlights: This is the first study showing that red fruit oil (RFO) stimulates nitric oxide production in endothelial cells. RFO contains highly potent substances stimulating eNOS activity and inducing vasodilation. RFO also reduces oxidative stress and prevents oxidative DNA damage in endothelial cells. Abstract: Red fruit oil (RFO) is used in traditional medicine for the treatment of a number of diseases. However, evidence for the biological effects and action mechanisms is still lacking. In the present study, we show for the first time that RFO stimulated the phosphorylation of the endothelial nitric oxide synthase (eNOS) and enhanced the NO production in human endothelial cells. In isolated mouse aorta, RFO induced a vasodilation, with a significant effect evident at a concentration as low as 1:100, 000 dilution. The RFO-induced vasodilation could be completely prevented by eNOS inhibition, indicating that RFO contains highly potent substances stimulating eNOS activity. In addition, RFO reduced oxidative stress in endothelial cells, as demonstrated with three different methods. In the comet assay, RFO significantly decreased oxidative DNA damage induced by genotoxicants. These results suggest that enhanced endothelial NO production and reduced oxidative stress may represent part of the molecular mechanisms responsible for the therapeutic effects of RFO.